Double carboxyl silicane modified graphene oxide coated silica composite as sorbent for solid-phase extraction of quarternary alkaloids. Issue 1 (10th November 2014) - Liu, Houmei; Guo, Yong; Wang, Xusheng; Li, Yikun; Liang, Xiaojing; Liu, Xia
Abstract : TSPSAcide@GO@SiO2 has been prepared and used as a sorbent for solid-phase extraction of quarternary alkaloids. Abstract : In this paper, a novel sorbent, double carboxyl silicane modified graphene oxide coated silica has been prepared and used as sorbent for solid-phase extraction of quarternary alkaloids. The synthesized sorbent material was characterized by elemental analysis and field emission scanning electron microscopy. The extraction properties of the developed sorbent were evaluated by four quarternary alkaloids: coptisine chloride, sanguinarine, berberine chloride and chelerythrine. Multiple interactions, i.e., electrostatic, hydrogen bonding and dipole–dipole interactions, take place during the extraction. After the optimization of conditions, several parameters, such as volume of sample loading, pH of sample, pH of eluent and sample loading velocity, were set up. Under the optimal conditions, good linearities with R 2 ranging from 0.9990 to 0.9995 were obtained for the four compounds. The LODs were found to be in the range of 1–2 μg L −1, and the LOQs were found to be in the range of 2–5 μg L −1 . The recoveries of the four quarternary alkaloids spiked with 5 μg L −1 in human urine samples ranged from 89.1% to 110.6% with RSDs in the range of 2.6–10.4%. The results showed that the new sorbent has excellent extraction capacity for the tested quarternary alkaloids.